The ingestion of a caffeinated energy drink improves jump performance and activity patterns in elite badminton players - Abian, P.; Del Coso, J.; Salinero, J. J.; Gallo-Salazar, C.; Areces, F.; Ruiz-Vicente, D.; Lara, B.; Soriano, L.; Munoz, V.; Abian-Vicen, J. (Journal of Sports Sciences, 2015)
The aim of this study was to investigate the effectiveness of a caffeine-containing energy drink to enhance physical and match performance in elite badminton players. Sixteen male and elite badminton players (25.4 ± 7.3 year; 71.8 ± 7.9 kg) participated in a double-blind, placebo-controlled and randomised experiment. On two different sessions, badminton players ingested 3 mg of caffeine per kg of body mass in the form of an energy drink or the same drink without caffeine (placebo). After 60 min, participants performed the following tests: handgrip maximal force production, smash jump without and with shuttlecock, squat jump, countermovement jump and the agility T-test. Later, a 45-min simulated badminton match was played. Players` number of impacts and heart rate was measured during the match. The ingestion of the caffeinated energy drink increased squat jump height (34.5 ± 4.7 vs. 36.4 ± 4.3 cm; P < 0.05), squat jump peak power (P < 0.05), countermovement jump height (37.7 ± 4.5 vs. 39.5 ± 5.1 cm; P < 0.05) and countermovement jump peak power (P < 0.05). In addition, an increased number of total impacts was found during the badminton match (7395 ± 1594 vs. 7707 ± 2033 impacts; P < 0.05). In conclusion, the results show that the use of caffeine-containing energy drink may be an effective nutritional aid to increase jump performance and activity patterns during game in elite badminton players.